Experiencing Uncommon Faithfulness:: Narrative Ecclesiology as Challenge and Promise - Stephen Nicholson, SJ, (Lumen et Vita, 2020)
The challenges confronting the church in the 21st century, especially that of persistent systemic racism, call for a methodological shift in ecclesiology. This paper explores the meaning and benefits of Natalia’s Imperatori-Lee’s narrative ecclesiology within the context of race in the United States Catholic Church. By turning to the story of God’s people, especially the silenced and oppressed, ecclesiology is empowered to challenge false histories and overturn theologies which justify oppression. Furthermore, the work of the Holy Spirit and the responses of the faithful are made evident in lives of “uncommon faithfulness,” such as those of Black Catholics in the US. To be guided by narrative ecclesiology today, members of the church must engage in an embodied struggle for liberation and so hear the story of God’s people anew.